Cycloadditions of Alkenylboronic Derivatives - Grygorenko, Oleksandr O.; Moskvina, Viktoriia S.; Hryshchuk, Oleksandr V.; Tymtsunik, Andriy V. (Synthesis, 2020)
The literature on cycloaddition reactions of boron-containing alkenes is surveyed with 132 references. The data are categorized according to the reaction type ([2+1], [2+2], [3+2], [4+2], and [4+3] cycloadditions). The cyclopropanation and the Diels–Alder reactions of alkenylboronic derivatives have been studied more or less comprehensively, and for some substrates, they can be considered as convenient methods for the rapid regio- and stereoselective construction of even complex cyclic systems. Other types of the cycloadditions, as well as mechanistic aspects of the processes, have been addressed less thoroughly in the previous works.1 Introduction2 [2+1] Cycloaddition2.1 Cyclopropanation2.1.1 With Methylene Synthetic Equivalents2.1.2 With Substituted Carbenoids2.2 Epoxidation2.3 Aziridination3 [2+2] Cycloaddition4 [3+2] Cycloaddition4.1 With Nitrile Oxides4.2 With Diazoalkanes4.3 With Nitrones4.4 With Azomethine Ylides5 [4+2] Cycloaddition6 [4+3] Cycloaddition7 Conclusions and Outlook
Keywords: organoboron compounds; cycloaddition; cyclopropanation; cyclobutanes; 1,3-dipolar cycloaddition; Diels–Alder reaction